A Guide to the Dagum Distributions - Christian Kleiber (University of Basel, Center of Business and Economics (WWZ), 2007)
In a series of papers in the 1970s, Camilo Dagum proposed several variants of a new model for the size distribution of personal income. This Chapter traces the genesis of the Dagum distributions in applied economics and points out parallel developments in several branches of the applied statistics literature. It also provides interrelations with other statistical distributions as well as aspects that are of special interest in the income distribution eld, including Lorenz curves and the Lorenz order and inequality measures. The Chapter ends with a survey of empirical applications of the Dagum distributions, many published in Romance language periodicals.
Keywords: 330; Einkommensverteilung; Statistische Verteilung; Theorie